Design and validation of enterprise application architectures [Diseño y validación de arquitecturas de aplicaciones empresariales] - Romero, F. (2015)
This work presents the results of the process of design and assessment of the enterprise applications using the Architectural Description Method ADM- TOGAF and an Architectural Description Language ADL. In order to get the results, a fundamental concern is getting the business architecture based on the structure and business process and its adaptation to Kruchten ?s 4+1 architectural model, that was used for representing the actual and future state of the applications architecture according to the requirements obtained during the ADMs architecture capability iteration. As a result we have a SOA based applications architecture considering the use of ESB. The architecture model was implemented in Java code within a high level ESB Enterprise Service Bus abstraction that allows it ?s future design and validation using the ADL Sonargraph Architect tool.